2013
DOI: 10.1073/pnas.1222341110
|View full text |Cite
|
Sign up to set email alerts
|

Auditory ganglion source of Sonic hedgehog regulates timing of cell cycle exit and differentiation of mammalian cochlear hair cells

Abstract: Neural precursor cells of the central nervous system undergo successive temporal waves of terminal division, each of which is soon followed by the onset of cell differentiation. The organ of Corti in the mammalian cochlea develops differently, such that precursors at the apex are the first to exit from the cell cycle but the last to begin differentiating as mechanosensory hair cells. Using a tissuespecific knockout approach in mice, we show that this unique temporal pattern of sensory cell development requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 32 publications
7
111
1
Order By: Relevance
“…Both Gli3-deficient cochlea and cochlear explants treated with chemical inhibitors of Shh signaling display an expanded prosensory domain, whereas Shh treatment prevents prosensory domain formation (Driver et al, 2008). Using a transgenic approach, it was shown that the ablation of Shh from the spiral ganglia at several developmental time points causes premature cell cycle exit and an abnormal wave of hair cell differentiation extending from the apex towards the base, in the opposite direction to normal development (Bok et al, 2013). In another study, Tateya and colleagues demonstrated that the conditional ablation of Smo in the developing cochlear epithelium results in accelerated hair cell differentiation in the apical region (Tateya et al, 2013).…”
Section: Shh Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Gli3-deficient cochlea and cochlear explants treated with chemical inhibitors of Shh signaling display an expanded prosensory domain, whereas Shh treatment prevents prosensory domain formation (Driver et al, 2008). Using a transgenic approach, it was shown that the ablation of Shh from the spiral ganglia at several developmental time points causes premature cell cycle exit and an abnormal wave of hair cell differentiation extending from the apex towards the base, in the opposite direction to normal development (Bok et al, 2013). In another study, Tateya and colleagues demonstrated that the conditional ablation of Smo in the developing cochlear epithelium results in accelerated hair cell differentiation in the apical region (Tateya et al, 2013).…”
Section: Shh Signalingmentioning
confidence: 99%
“…The availability of genetic tools has enabled us to further dissect components of these pathways. Moreover, these studies have begun to reveal the complex interplay that exists among different pathways at different developmental stages, ranging from otic placode specification (Jayasena et al, 2008) and sensory cell specification (Benito-Gonzalez and Doetzlhofer, 2014;Bok et al, 2013;Munnamalai et al, 2012;Tateya et al, 2013) to the maintenance of cell fate (Doetzlhofer et al, 2009;Li et al, 2015). As insights into the roles of additional pathways in these diverse contexts culminate (e.g.…”
Section: Future Perspectives Exploring the Intersections Between Signmentioning
confidence: 99%
“…How might LIN28B alter the timing of HC differentiation? To date two pathways, the Insulin-like growth factor (Igfr1)-phosphatidylinositol 3-kinase (PI3K)/Akt pathway and the Shh pathway, have been shown to influence timing of HC differentiation within the murine cochlea (65)(66)(67)73). LIN28B has been shown to positively regulate Igf1r-PI3K/Akt pathway (27); however, loss of Igfr1 within the developing cochlea does not mirror LIN28B's effects on HC differentiation.…”
Section: Lin28b Acts Through a Let-7-dependent Mechanism To Time Prosmentioning
confidence: 99%
“…Shh required for cochlear development is sequentially secreted by two different sources: initially from the floor plate and notochord in the ventral midline and later from the spiral ganglion neurons starting at E11.75 (15,24). We thus asked which source(s) of Shh mediate the specification of regional cochlear identity.…”
Section: Regional Cochlear Identity Is Specified Early By Shh Emanatimentioning
confidence: 99%
“…However, testing this hypothesis using a loss-of-function approach is not feasible because the cochlea fails to form in the absence of Shh in both species, which precludes tonotopic analyses (8)(9)(10). In mice, tonotopic analysis is further confounded because most of the mutant mice do not survive until postnatal day 4, when the morphological differences in sensory hair cells can be first observed (5,8,10,14,15).…”
mentioning
confidence: 99%